Best Answer

6x + 6 = 3x - 2 Bring 3x to the left and subtract: 6x - 3x = 3x 3x + 6 = -2 -2 - 6 = -8 -8 / 3 X = -8/3

Study guides

☆☆

Q: Solve the equation for x 6x plus 6 equals 3x - 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

3x-2 = 2x+3 3x-2x = 3+2 x = 5

3x+4=10 To solve: 3x+4=10 3x=6 x=2

Add 5 to both sides of the equation to get rid of the - 5. -3x - 5 + 5 = -20 + 5 Solve and simplify. -3x = -15 Divide both sides of the equation by -3. x = 5

The given equation: =3x-4x plus 9xy-12y =3x-4x+9xy-12y =-x+9xy-12y =-x+3y(3y-4) Answer.

The elimination method only works with simultaneous equations, hence another equation is needed here for it to be solvable.

Related questions

x = 6

3x+5=20 3x=15 x=5

X = 12

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

First, subtract 3x from each side of the equation. Then, divide each side of the equation by 7 .

You cannot solve one linear equation in two unknown variables.

3x-2 = 2x+3 3x-2x = 3+2 x = 5

5x+y=-7 3x+y=15 8=D

3x+4=10 To solve: 3x+4=10 3x=6 x=2

15x minus 8=minus 180 3x+8=24

2y-3x=4

From second equation: y = 8 + 2xSubstitute for y in first equation: 3x + 16 + 4x = 2ie 7x = -14ie x = -2 and y = 4

People also asked

Featured Questions